3D Chiral Photonic Nanostructures Based on Blue‐Phase Liquid Crystals. Issue 6 (5th May 2021) - Yang, Yanzhao; Wang, Ling; Yang, Huai; Li, Quan
Abstract : 3D photonic nanostructures with intrinsic chirality have recently entered the research limelight due to their fundamental importance and potential technological applications. Blue‐phase liquid crystals (BPLCs) with chiral cubic nanostructures are an inventive example of 3D chiral photonic nanostructures. The inherently self‐organized 3D chiral nanostructures give rise to a complete photonic bandgap, which results in the selective reflection of circularly polarized light in all three dimensions. Herein, a comprehensive review of the state‐of‐the‐art of BPLCs and their potential applications is presented. First, the history and fundamentals of BPLCs are introduced. Then, the recent endeavors in the design, synthesis, and properties of BPLCs such as lattice orientation control with different techniques, photonic bandgap tuning with external fields, and fabrication of free‐standing BPLC polymer films are summarized. Finally, a discussion of the future challenges and potential applications of BPLCs is provided. It is believed that this review would stimulate innovative ideas for the design and engineering of novel chiral nanostructured materials for advanced photonic systems with tailorable functionalities. Abstract : 3D chiral photonic nanostructures are of great significance due to the presence of a complete photonic bandgap and omnidirectional selective reflection of circularly polarized light. Herein, an account on the state‐of‐the‐art in blue‐phase liquid crystals with chiral cubic nanostructures and their potential applications is provided. In addition, perspectives for future scope, challenges, and opportunities for such a multidisciplinary topic are presented.